2021
DOI: 10.1016/j.ijid.2021.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes of pregnant women with drug-resistant tuberculosis in Uganda: A retrospective review of 18 cases

Abstract: Background: There is a dearth of reports on drug-resistant tuberculosis (DRTB) treatment outcomes among pregnant women in tuberculosis (TB)/HIV high-burdened countries. We report treatment outcomes of 18 pregnant women with DRTB in Uganda. Methods: We reviewed charts of individuals who received DRTB treatment in Uganda across 16 DRTB treatment sites. We included all women who were pregnant during DRTB treatment and had a treatment outcome documented between 2013 and 2019. Results: There were 18 pregnant women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Our electronic database searches identified 487 records. After removal of duplicates, excluding studies by title and abstract screening and full-text review (eTable 5 in the Supplement ), 10 studies 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 were included in the meta-analysis, which included 288 pregnant patients with MDR-TB ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our electronic database searches identified 487 records. After removal of duplicates, excluding studies by title and abstract screening and full-text review (eTable 5 in the Supplement ), 10 studies 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 were included in the meta-analysis, which included 288 pregnant patients with MDR-TB ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The studies were conducted in 5 different countries, and the data were collected from 1996 to 2019 (eTable 6 in the Supplement ). Among the included studies, 9 were published in English, 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 and 1 was in Spanish. 23 Treatment outcomes were reported for all 10 studies, which included 275 of the 288 pregnant patients with MDR-TB ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The management of DRTB in Uganda during the period under evaluation is described elsewhere. [33][34][35]…”
Section: Study Setting and Populationmentioning
confidence: 99%
“…However, this recommendation is generally based on observational studies, and adequately powered randomised control trials are required to investigate the safety, tolerability and effectiveness, as well as the timing and duration, of a drug in pregnancy before widely recommending the drug for use in national TB programmes. A recent study from South Africa showed that bedaquiline exposure during pregnancy was not significantly associated with fetal and neonatal deaths, but was associated with low birthweight, which is an indication for further investigation 3 …”
Section: Disclosure Of Interestsmentioning
confidence: 97%
“…Jana and colleagues have also suggested the use of the most effective regimens, including bedaquiline, for the treatment of MDR‐TB during pregnancy. Here, it is important to note that although pregnancy is not a contraindication for the treatment of MDR‐TB, the management of MDR‐TB during pregnancy is complex, lengthy and associated with adverse birth outcomes 3 . The safety and effectiveness of most second‐line TB medications have not been well studied as pregnant women have been generally excluded from experimental studies because of safety concerns 4 .…”
Section: Disclosure Of Interestsmentioning
confidence: 99%